Correction: The NADPH Oxidase Complexes in Botrytis cinerea: Evidence for a Close Association with the ER and the Tetraspanin Pls1. - Ulrike Siegmund (Public Library of Science (PLoS), 2013)
[This corrects the article on p. e55879 in vol. 8.].